Spring-water temperature suggests widespread occurrence of Alpine permafrost in pseudo-relict rock glaciers - Carturan, Luca; Zuecco, Giulia; Andreotti, Angela; Boaga, Jacopo; Morino, Costanza; Pavoni, Mirko; Seppi, Roberto; Tolotti, Monica; Zanoner, Thomas; Zumiani, Matteo (The Cryosphere, 2024)
Runoff originating from ground ice contained in rock glaciers represents a significant water supply for lowlands. Pseudo-relict rock glaciers contain patchy permafrost but appear to be relict, and therefore they can be misinterpreted when using standard classification approaches. The permafrost content, spatial distribution and frequency of this type of rock glacier are poorly known. Therefore, identifying pseudo-relict rock glaciers that might still contain permafrost, and potentially ice, is crucial for understanding their hydrological role in a climate change context. This work analyses rock–glacier spring-water temperature in a 795 km2 catchment in the eastern Italian Alps to understand how many rock glaciers classified as relict could have spring-water temperatures comparable to active or transitional rock glaciers as possible evidence of their pseudo-relict nature. Spring-water temperature, often auxiliary to other approaches for specific sites, was used for a preliminary estimate of the permafrost presence in 50 rock glaciers classified as relict. In addition, we present electrical resistivity tomography (ERT) results on two relict rock glaciers with opposing spring-water temperature and surface characteristics to constrain spring-water temperature results at the local scale. The results show that about 50 % of the rock glaciers classified as relict might be pseudo-relict, thus potentially containing permafrost. Both supposedly relict rock glaciers investigated by geophysics contain frozen sediments. The majority of the cold springs are mainly associated with rock glaciers with blocky and scarcely vegetated surfaces, but geophysics suggest that permafrost may also exist in rock glaciers below 2000 m a.s.l., entirely covered by vegetation and with a spring-water temperature of up to 3.7 °C. We estimate that pseudo-relict rock glaciers might contain a significant portion (20 %) of all the ice stored in the rock glaciers in the study area. These results highlight the relevance of pseudo-relict rock glaciers ...